Antibacterial activity, optical, and functional properties of corn starch-based films impregnated with bamboo leaf volatile oil. (30th September 2021) - Wang, Bin; Yan, Shouxin; Gao, Wei; Kang, Xuemin; Yu, Bin; Liu, Pengfei; Guo, Li; Cui, Bo; Abd El-Aty, A.M.
Highlights: BVO was incorporated into starch films using a solution casting method. EAB and surface roughness are improved by adding BVO to as-prepared films. The addition of BVO can reduce the TS, MC, and WVP. Adding BVO to corn starch films can reduce gloss. Corn starch-based films formulated with BVO showed an antimicrobial effect. Abstract: In this study, the optical, morphological, antibacterial, and physical properties of corn starch-based films prepared by a solution casting method were investigated after adding various levels of bamboo leaf volatile oil (BVO, 0.5, 1, and 2%). Further, the roughness was measured by atomic force microscopy and the antibacterial activities were tested by agar diffusion method. We found that the thickness (TC) and elongation at break (EAB) of the corn starch-based films increased significantly (Duncan's range test, P < 0.05) with the addition of BVO (TC from 0.121 to 0.207 mm; EAB from 2.48 to 10.40%). However, with the addition of BVO, the moisture content (MC) and water-solubility decreased (MC: from 13.12 to 11.41%; water solubility: from 30.58 to 26.95%), and the water vapor permeability (WVP) and tensile strength (TS) decreased significantly (WVP: from 3.91 to 3.05 g m m −2 s −1 Pa −1 ; TS: from 20.64 to 10.68 MPa, Duncan's range test, P < 0.05). Furthermore, supplementation of BVO to corn starch-based films increased the surface roughness and the antibacterial effects. The addition of BVO also increases the opacity of the films, which is helpful to protect food from ultraviolet damage. In sum, this study provides a theoretical basis for using corn starch-based films as alternative packing biomaterial.